Detection of precursory signals of past earthquakes using integration of spatio-temporal parameters - Alvan, Habibeh Valizadeh (2013)
The preparation process of an impending earthquake may leave fingerprints on the earth’s surface. Earthquakes are triggered when the energy accumulated in rocks releases causing ruptures in the ground or movements in place of the existing faults. Elastic strain in rocks, formation of micro-cracks, gas releases and other chemical or physical activities in the earth’s crust before and during earthquakes has been reported to cause rises in temperature, surface latent heat flux (SLHF), upwelling index and chlorophyll-a (Chl-a) concentration on the ground or sea surface. This study examines variations of the mentioned factors before several past oceanic, coastal earthquakes occurred at the Pacific and Indian Oceans together with two pairs of successive inland earthquakes in Kerman and Azerbaijan provinces, Iran. The sudden partial releases of the elastic energy which has resulted to the main events are believed to be detected by seismographs and remote sensing techniques. Pre-earthquake anomalies prior to all case study earthquakes were detected. Our detailed analyses on oceanic/coastal earthquakes revealed 1–5°C rises in surface temperature in epicenter areas. Considerable anomalies in Chl-a concentration, five weeks to a day before the earthquake events which are accompanied by the raises in upwelling indices were detected. Time series of SLHF also showed meaningful rises from one month to one week before the main events. The anomalous patterns started developing several weeks before earthquakes and disappeared after the main shocks. Significant rises in SLHF may lead us to understand the energy exchange mechanism during earthquakes and at the period of aftershocks, as well. The most interesting factor which yielded considerable results for almost all earthquake instances was SLHF. In case of offshore and coastal earthquakes the Chl-a was found to be the most common precursor. Most of the anomalous patterns were in accordance with local and regional active faults which have been already proposed as triggering structures by international research organizations. The seismographic records were also successfully used for confirmation of the earth’s movements during the preparation stage of the main event of Ahar as an underlying cause for remotely sensible phenomena. The author strongly believes that with proper use of remote sensing data, expert analysis of seismographs from nearby stations (which unfortunately are not existing everywhere), advanced in-situ measurement devices, and thorough information about local and regional active faults developing local earthquake prediction systems for earthquake prone region would not be impossible.